2021
DOI: 10.1001/jamanetworkopen.2021.35975
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 Antibodies Among Children in School and Day Care in Montreal, Canada

Abstract: Key Points Question What is the seroprevalence of SARS-CoV-2 antibodies in a convenience sample of children aged 2 to 17 years in Montreal, Canada, enrolled between October 2020 and March 2021? Findings In this cohort study of 1632 participants, the mean baseline seroprevalence of SARS-CoV-2 was 5.8%. Of the 95 participants who were seropositive for SARS-CoV-2 antibodies, 82% were not tested or tested negative, and all experienced either mild or no clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
8
27
6
Order By: Relevance
“…In this study, higher seroprevalence in those with a history of laboratory-confirmed COVID-19 was not observed. However, only 2.4% of the participants had a known history of COVID-19, a finding which agrees with previous studies suggestive of a significantly higher frequency of asymptomatic infections and undertesting in children than in adults [ 21 , 22 ]. A population-based study in Geneva also observed lower seroprevalence rates among younger (6–9 years old) children [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, higher seroprevalence in those with a history of laboratory-confirmed COVID-19 was not observed. However, only 2.4% of the participants had a known history of COVID-19, a finding which agrees with previous studies suggestive of a significantly higher frequency of asymptomatic infections and undertesting in children than in adults [ 21 , 22 ]. A population-based study in Geneva also observed lower seroprevalence rates among younger (6–9 years old) children [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Since the start of the COVID-19 pandemic, it has become apparent that pediatric populations are less affected than adult or older populations (1,2), although studies have also found children and adults to be infected to a similar low degree (3). Clinical presentation of SARS-CoV-2 infection is milder in children, with more proportion of asymptomatic cases (1,(4)(5)(6). One hypothesis for this lower severity of COVID-19 is the protective effect that antibodies from human coronaviruses of the common cold (HCoV), which are more prevalent in children, could exert on SARS-CoV-2 control, considering cross-reactivity between them (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Both calculations are based on power of 80% and a two-sided significance level of 95%. Using the eligible student populations of the sampled primary and secondary schools, we require response rates of 6% and 28% among parents and adolescents, respectively, which are reasonable targets based on our previous COVID-19 research in Montreal schools 31…”
Section: Methods and Analysismentioning
confidence: 99%